Forgiveness as a mediator on the effect of self-compassion on the ego depletion - Rahman, Agus Abdul; Arisanti, Elvariana Valencia; Prahastuti, Nurul Fajriyah; Djamal, Nani Nuranisah (Psikohumaniora: Jurnal Penelitian Psikologi, 2019)
Self-compassion is a trait that helps people to withstand stressful situations. Self-compassion helps people to maintain self-regulation, to interpret the positive side of the problems, and to avoid ego depletion. The purpose of this research is to examine the indirect effect of self-compassion to ego depletion with forgiveness as a mediating variable. Forgiveness selected as a mediating variable because of its ability to play a role as a coping strategy and reduce ego depletion tendency. The researcher believes that the impact of self-compassion to ego depletion increasing if forgiveness included as a mediating variable. This research used a regression technique analysis. Data were collected on 200 students by purposive sampling technique using a self-compassion scale, ego depletion scale, and forgiveness scale. The result shows that the impact of self-compassion to ego depletion decreased without forgiveness as a mediating variable. The researcher concluded that forgiveness was effective as a mediating variable to self-compassion and ego depletion.